Urban (pre)Occupation. Rearguard cooperation in modern warfare: Madrid, 1939 - Píriz, Carlos (Hispania Nova, 2021)
Before the Francoist occupation troops entered Madrid in late March 1939 after two and a half years of siege, his collaborators and the agents of his secret services ambushed in the city had seized the capital of Spain. This process of rearguard cooperation prior to the invasion of a large modern city is called in these pages “urban (pre) occupation”. After a brief tour of the history of the main clandestine organizations that these accomplices of the assailants created in order to win the war in the Republican territory and who were called “Fifth Column”, this article demonstrates for the first time how it was thought, managed and implemented the internal seizure of the city, which was handed over to the invading army without incident.
Keywords: urban (pre)Occupation; fifth column; secret service; spanish civil war; Madrid